Clostridial necrotic enteritis: field cases and the role of vaccination against coccidiosis to the incidence in broiler chicken - Lily Natalia; A Priadi (Jurnal Ilmu Ternak dan Veteriner, 2003)
A study of necrotic enteritis in broiler chicken was carried out in West Java. Isolates of highly toxigenic C. perfringens of type C were isolated from field cases of necrotic enteritis which most frequently occured in chicken with vaccine-inducedcoccidial lesions. Experimental study in broiler chicken was conducted to determine the predisporing factor for necroric enteritis. Three possible factors were evaluated, those were feeding with high animal protein ingreadients, vaccination with live attenuated anticoccidial vaccine, and feeding with spores of C. perfringens type A and C. The occurrence of intestinal coocidial leions in chicks vaccinated with life attenuated anticoccidial vaccine was demonstrated. The highest mortality and the significant intestinal lesions of chickens were observed in group treated with live attenuated anticoccidial vaccine and C. perfringens type A and C spores (P<0.01). From the experiment, it was found that vaccine induced-coccidial lesions and C. perfringens type A and C were the predisposing factors of necrotic enteritis. These results suggest that the concurrent infection with coccidia and C. perfringens has a synergistic effect on mortality and intestinal lesions in necrotic enteritis.   Key words : Clostridial necrotic enteritis, broiler chicken, coccidiosis